Fatty Acid Binding Proteins 3 and 4 Predict Both All-Cause and Cardiovascular Mortality in Subjects with Chronic Heart Failure and Type 2 Diabetes Mellitus - Ricardo Rodríguez-Calvo; Minerva Granado-Casas; Alejandra Pérez-Montes de Oca; María Teresa Julian; Mar Domingo; Pau Codina; Evelyn Santiago-Vacas; Germán Cediel; Josep Julve; Joana Rossell; Lluís Masana; Didac Mauricio; et al. (MDPI AG, 2023)
Subjects with type 2 diabetes mellitus (T2D) are at increased risk for heart failure (HF). The cardiac-specific (FABP3) and adipose-tissue-specific (FABP4) types of the fatty acid binding proteins have been associated with both all-cause and cardiovascular (CV) mortality. The aim of this study was to explore the prognosis value of FABP3 and FABP4 in ambulatory subjects with chronic HF (CHF), with and without T2D. A prospective study involving 240 ambulatory CHF subjects was performed. Patients were followed-up for a mean of 5.78 ± 3.30 years and cause of death (if any) was recorded. Primary endpoints were defined as all-cause and CV death, and a composite endpoint that included CV death or hospitalization for HF was included as a secondary endpoint. Baseline serum samples were obtained and the serum FABP3 and FABP4 concentrations were assessed by sandwich enzyme-linked immunosorbent assay. Survival analysis was performed with multivariable Cox regressions, using Fine and Gray competing risks models when needed, to explore the prognostic value of FABP3 and FABP4 concentrations, adjusting for potential confounders. Type 2 diabetes mellitus was highly prevalent, accounting for 47.5% for total subjects with CHF. Subjects with T2D showed higher mortality rates (T2D: 69.30%; non-T2D: 50.79%, p = 0.004) and higher serum FABP3 (1829.3 (1104.9-3440.5) pg/mL vs. 1396.05 (820.3-2362.16) pg/mL, p = 0.007) and FABP4 (45.5 (27.6-79.8) ng/mL vs. 34.1 (24.09-55.3) ng/mL, p = 0.006) concentrations compared with non-T2D CHF subjects. In the whole study cohort, FABP3 was independently associated with all-cause death, and both FABP3 and FABP4 concentrations were associated with CV mortality. The predictive values of these two molecules for all-cause (FABP3: HR 1.25, 95% CI 1.09-1.44; p = 0.002. FABP4: HR 2.21, 95% CI 1.12-4.36; p = 0.023) and CV mortality (FABP3: HR 1.28, 95% CI 1.09-1.50; p = 0.002. FABP4: HR 4.19, 95% CI 2.21-7.95; p < 0.001) were only statistically significant in the subgroup of subjects with T2D. Notably, FABP4 (HR 2.07, 95% CI 1.11-3.87; p = 0.022), but not FABP3, also predicted the occurrence of the composite endpoint (death or hospitalization for HF) only in subjects with T2D. All these associations were not found in CHF subjects without T2D. Our findings support the usefulness of serum FABP3 and FABP4 concentrations as independent predictors for the occurrence of all-cause and CV mortality in ambulatory subjects with CHF with T2D.